Simvastatin Restores HDAC1/2 Activity and Improves Behavioral Deficits in Angelman Syndrome Model Mouse - Kumar, Vipendra; Joshi, Tripti; Vatsa, Naman; Singh, Brijesh Kumar; Jana, Nihar Ranjan (Frontiers in Molecular Neuroscience, 2019)
Angelman syndrome (AS) is a neurodevelopmental disorder categorized by severe disability in intellectual functions and affected by the loss of function of maternally inherited UBE3A gene. Mice deficient for the maternal Ube3a recapitulates many distinguishing behavioral features of the AS and is used as a typical model system to understand the disease pathogenic mechanism. Here, we first show a significant increase in HDAC1 and HDAC2 activities in AS mice brain from as early as embryonic day 16(E16). In depth study further reveals that the deficiency of Ube3a leads to transcriptional up-regulation of both HDAC1 and HDAC2. Restoration of HDAC1 and HDAC2 activities (as evident from the increased acetylation of histones H3 and H4) using simvastatin significantly improves the cognitive deficit and social interaction behavior in AS mice. Simvastatin treatment also restores the reduced level of BDNF in AS mice brain. Finally, we demonstrate that the treatment of simvastatin to primary cortical neuronal culture prepared from AS mice embryo also rescues altered acetylation of histones H3 and H4 and the level of BDNF. These results suggest that simvastatin could be a promising drug for the treatment of AS.